(untitled) (Journal of the College of Basic Education, 2022)
The current research includes the semantics of expression for the textual structure in the compositions of the thuluth calligraphy four chapters and according to the methodology followed, where the first chapter is devoted to the research problem, which the researcher has identified by studying the semantics of expression in the written text and what these connotations symbolize, then the importance of the research and its goal, then the objective, temporal and spatial research limits in Egypt, Iraq and Turkey From 2004-2012 AD Then defining the term, and the second chapter was divided into two topics. The first is on two axes devoted to the concept of semantics in art and expression in written text, while the second topic talks about the forms of semantics of expression in the compositions of the third line and the third chapter is devoted to research procedures and analysis of samples, while the fourth chapter is devoted to results, recommendations and proposals, then margins Arab and foreign research and sources